A MnFe based Prussian blue Analogue@Reduced graphene oxide composite as high capacity and superior rate capability anode for lithium-ion batteries. (March 2019) - Sun, Daming; Wang, Hao; Deng, Bangwei; Zhang, Huan; Wang, Lei; Wan, Qi; Yan, Xinxiu; Qu, Meizhen
Abstract: Prussian blue analogues (PBAs) have attracted increasing attention in energy research due to their open frameworks and short channels. However, the practical application of PBAs as anode materials for lithium-ion batteries (LIBs) is severely limited by their low capacity and poor cycling performance. In this work, a MnFe based Prussian blue analogue@reduced graphene oxide (Mn-PBA@rGO) composite is prepared via an in-situ synthesis process to maximum using the residual manganese ions in the GO suspension. The Mn-PBA nanoparticles (NPs) anchor tightly on the rGO layers that form a conductive network in the composite. The forceful synergistic effect between the highly conductive N-doped rGO layers and Mn-PBA NPs can efficaciously mitigate the structural collapse and aggregation during the insertion and extraction of Li + . Because of above merits, the Mn-PBA@rGO composite exhibits a high reversible capacity of 1167.7 mAh g −1  at a current density of 0.1 A g −1 and superior rate capability, delivering capacities of 844.0, 594.5, and 400.1 mAh g −1  at 3, 5, and 10 A g −1, respectively. The specific capacities at 3, 5 and 10 A g −1 can be equal to the initial one even after 1000 cycles, thus indicating that it is a promising anode material for LIBs. Graphical abstract: MnFe based Prussian blue analogue nanoparticles anchor tightly on N-doped reduced-Graphene Oxide layers (Mn-PBA@rGO) as an new anode material for Lithium-ion batteries (LIBs). It exhibits ultrahigh capacity, long cycle lifetime and superior rate performance and may also be used in other energy conversion and storage device that require high power output and fast response, such as supercapacitor.